Exploring the efficacy and safety of laparoscopic liver resection in the treatment of early-stage male patients with liver cancer and tumor diameter ≤5 cm - Shipeng Cui (Journal of Men's Health)
Background: This study investigates the efficacy and safety of laparoscopic hepatectomy in male patients with hepatocellular carcinoma (HCC) and tumor diameter ≤5 cm. Methods: The clinical data of 100 male HCC patients treated at our hospital from January 2019 to January 2021 were retrospectively collected. According to the treatment methods, patients were divided into an observation group (50 cases) and a control group (50 cases). The control group underwent traditional open non-anatomical liver resection, while the observation group received laparoscopic non-anatomical liver resection. The safety and efficacy of the two surgical methods were compared. Results: The observation group demonstrated significantly reduced intraoperative blood loss, operation time, incision length, and hepatic portal occlusion time than the control group (p < 0.001). The observation group had shorter times to mobilization, initiation of oral feeding, and hospital discharge (p < 0.001). On postoperative day three, levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and total bilirubin (TBIL) were significantly lower in the observation group (p < 0.05). Cluster of Differentiation 3+ (CD3+), CD4+, CD8+, and CD4+/CD8+ ratio were improved in the observation group one week post-surgery (p < 0.05). The complication rate was significantly lower in the observation group (p < 0.05). At 1 and 3 years post-surgery, the recurrence rate in the observation group was significantly lower (p < 0.05). The overall survival (OS) rates at one, two, and three years were 75.9%, 41.4% and 12.9% for the observation group and 55.5%, 14.4% and 0% for the control group (p < 0.05), respectively. The median survival times in the observation group was significantly longer than the control group (p < 0.05). Conclusions: Laparoscopic hepatectomy for HCC offers improved clinical outcomes, enhanced liver function, reduced complication rates, and favorable safety profiles compared to open hepatectomy.